"All Men Are Entitled to Justice By the Government": Black Workers, Citizenship, Letter Writing, and the World War I State. (1st September 2014) - Taillon, Paul Michel
Abstract: This article examines the letter writing of black railroad workers to the United States Railroad Administration during World War I. Engaging with scholarship on the African American experience during the war years, the article considers the ways in which ordinary African Americans acted on the opportunities presented by the mobilization for challenging Jim Crow and seeking racial justice. The article disagrees with interpretations that see the war period as one of promise but ultimately failure and disappointment for advocates of racial justice. Rather, attention to the epistolary undertakings of black railroaders reveals how letter writing itself figured as a form of political action through which black workers sought to bend the state to their purposes. The content of black railwaymen's letters demonstrates the importance of citizenship and the centrality of economic justice to civil rights activism. Moreover, these letters illustrate how letter writing could be empowering. Not only did black workers demand fair treatment at work but in the course of writing many of them also fashioned themselves as fully endowed citizens. In Jim Crow America, in a society and culture that publicly denied African Americans agency as well as basic rights and liberties, the capacity of letter writing to facilitate "self-narration" against dominant exclusionary definitions of citizenship helped African Americans, in the words of historian Chad Williams, "resist white supremacy, affirm their citizenship, and assert their humanity."